Smart Approach for Finding Indoor Navigation Using BLE for Visually Impaired Person - Mule, Kalyani; JV, Shinde (International Journal of Computer Sciences and Engineering, 2019)
In todays’ life, the problems faced by the visually impaired persons are increases due to the huge growth in urbanization in cities. Even a normal person also gets confused, if they come across to the new locations. To handle this problem, in this paper, we have proposed a new robust system, which provide help to user while navigating in big industrial buildings. This system uses BLE (bluetooth low energy) devices to communicate with the hardware present at user and then it will direct the route to the user. The process includes user interaction through voice for the input location after that system will find desired location of user by connecting the hardware to various BLE devices and depending upon the signal strengths from each BLE user will be get navigated. If the range of BLE devices get less than that means, that user is going away from that BLE device and similarly if the range of particular device is getting increase then it means that user going towards the BLE device. Now to get accurate result we are implementing Three Dimensional Triangulation Technique where the hardware present at user will simultaneously connect with multiple BLE devices and then find the required route for navigation. Along with this we are providing IR(infra-red) SONAR sensors through which we can find any obstacle that comes between the user and its navigation. We have added buzzer and LED lights to notify the obstacle to others.